2015
DOI: 10.1371/journal.pone.0128476
|View full text |Cite
|
Sign up to set email alerts
|

Bar-HRM for Authentication of Plant-Based Medicines: Evaluation of Three Medicinal Products Derived from Acanthaceae Species

Abstract: Medicinal plants are used as a popular alternative to synthetic drugs, both in developed and developing countries. The economic importance of the herbal and natural supplement industry is increasing every year. As the herbal industry grows, consumer safety is one issue that cannot be overlooked. Herbal products in Thai local markets are commonly sold without packaging or labels. Plant powders are stored in large bags or boxes, and therefore buying local herbal products poses a high risk of acquiring counterfei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 42 publications
3
42
0
Order By: Relevance
“…The first study reporting the use of Bar-HRM to study herbal medicine substitution has recently been reported in a study on species substitution among three medicinal species of Acanthaceae [84]. Bar-HRM has also been used in a number of comparable methodologies [85], such as for authentication of an EU Protected Designation of Origin product made from Lathyrus clymenum [86], olive oil and adulterants [87], subspecies cultivar identification in eggplant [88], identification of closely related species relevant to TDG [89,90], species distinction in Mediterranean pines [91], detection of allergenic hazelnut contamination [92], and processed bean crops [93][94][95].…”
Section: Bar-high Resolution Meltingmentioning
confidence: 99%
“…The first study reporting the use of Bar-HRM to study herbal medicine substitution has recently been reported in a study on species substitution among three medicinal species of Acanthaceae [84]. Bar-HRM has also been used in a number of comparable methodologies [85], such as for authentication of an EU Protected Designation of Origin product made from Lathyrus clymenum [86], olive oil and adulterants [87], subspecies cultivar identification in eggplant [88], identification of closely related species relevant to TDG [89,90], species distinction in Mediterranean pines [91], detection of allergenic hazelnut contamination [92], and processed bean crops [93][94][95].…”
Section: Bar-high Resolution Meltingmentioning
confidence: 99%
“…Therefore, DNA-based technologies, which are more stable and reliable, have clear advantage over these traditional methods. Although DNA barcoding, extreme PCR, or high-resolution melting analysis provide more authentic and accurate results, cost-effective and reliable identification tools like ISSR and RAPD markers have been considered advantageous since they can be carried out in reasonably equipped laboratories [19,[21][22][23]. In the present study, phylogenetic inference coupled with PCA and PCoA effectively resolved and clearly differentiated W. calendulacea from E. alba.…”
mentioning
confidence: 74%
“…HRM technology has been utilized for discriminating cultivated varieties, medicinal plant species, herbal tea, wine authenticity (Jung et al, 2010; Osathanunkul et al, 2015, 2016; Costa et al, 2016; Li et al, 2016; Song et al, 2016; Pereira et al, 2017). However, a reliable HRM approach to identify herbal medicines on Chinese herb market is still lacks.…”
Section: Resultsmentioning
confidence: 99%